PERSEPSI MAHASISWA JURUSAN MANAJEMEN TERHADAP KUALITAS FAKULTAS EKONOMI UNIVERSITAS NEGERI SEMARANG - Sutrasmawati, Endang (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
This reserach aim to know the perception of management student economics faculty about service quality to satisfaction. Raised ;there is positive influence and significance between reliability and satisfaction with coeffecient regression 0.737, there is positive influence and significance between responsiveness and satisfaction with coeffecient regression 0.572, there is positive influence and significance between emphaty and satisfaction with coeffecient regression 0.954, there is positive influence and significance between guarantee and satisfaction with coeffecient regression 0.162 there is positive physical evidence and significance between reliability and satisfaction with coeffecient regression 0549. Based o this research , the faculty management must give attention to emphaty variablebecause this variable can be influence the student satisfaction. Keywords: Service Quality , Perception management student